Small Horizontal Wind Turbine Design and Aerodynamic Analysis Using Q-Blade Software (Baghdad Science Journal, 2023)
Wind energy is one of the most common and natural resources that play a huge role in energy sector, and due to the increasing demand to improve the efficiency of wind turbines and the development of the energy field, improvements have been made to design a suitable wind turbine and obtain the most energy efficiency possible from wind. In this paper, a horizontal wind turbine blade operating under low wind speed was designed using the (BEM) theory, where the design of the turbine rotor blade is a difficult task due to the calculations involved in the design process. To understand the behavior of the turbine blade, the QBlade program was used to design and simulate the turbine rotor blade during working conditions. The design variables such as (chord length and torsion angle) affecting the performance of wind turbines were studied. Aileron (NACA4711) was selected for sixteen different sections of the blade with a length of (155 cm) both (power factor, torque coefficient, lift coefficient, drag coefficient, lift-to-drag coefficient ratio) where high-accuracy results were obtained and it was found that the best performance in which the turbine rotor can operate is when the(tip speed ratio) is equal to (7). In addition, a power factor was obtained (Cp = 0.4742), not exceeding the Betz limit (0.59%). It is good efficiency for a small wind turbine, and it turns out that the design of a small horizontal wind turbine with three blades is suitable for working in areas with low wind speed.